Staphylococcal Adhesion and Host Cell Invasion: Fibronectin-Binding and Other Mechanisms - Josse, Jérôme; Laurent, Frédéric; Diot, Alan (Frontiers in Microbiology, 2017)
Opportunistic bacteria from the genus Staphylococcus can cause life-threatening infections such as pneumonia, endocarditis, bone and joint infections and sepsis. This pathogenicity is closely related to their capacity to bind directly to the extracellular matrix or to host cells. Adhesion is indeed the first step in the formation of biofilm or the invasion of host cells, which protect the bacteria from the host immune system and facilitate chronic infection. Adhesion relies on the expression of a repertoire of surface proteins called adhesins, notably microbial surface components recognizing adhesive matrix mol¬ecules (MSCRAMMs). In this short review, we discuss the main pathway (FnBP-Fn-5ß1 integrin), as well as alternatives, through which Staphylococcus aureus adheres to and then invades non-professional phagocytic cells (NPPCs). We then examine the corresponding mechanisms for coagulase negative staphylococci. There is currently a little understanding of the molecular mechanisms that lead to internalization. Filling this gap in the literature would therefore be an important step towards limiting the duration of staphylococci infections in clinical practice.